PENGARUH KEPEMIMPINAN DAN KEDISIPLINAN TERHADAP KINERJA KARYAWAN PADA PT. DAIKIN AIR CONDITIONING CABANG MAKASSAR - Kurniawan, Ade; Sadariah, Sadariah (Universitas Ichsan Sidenreng Rappang, 2024)
Of this study is to determine the influence of leadership and discipline on employee performance at PT. Daikin Airconditiong Indonesia Makassar Branch. The types of data used in this study are qualitative and quantitative data. The data sources used in this study are primary data and secondary data. The analysis method used is descriptive analysis and statistical analysis through multiple linear regression tests obtained a value of Y = 9.956 + 0,393 X1 + 0,402 X2, then the value of the correlation coefficient (r) 0,830, or 83,0% and the coefficient of determination (r2) of 0,678 or 67,8%. Furthermore, the calculation of the T test obtained results for leadership variables, namely T count 4,091 > T table 1,673 and discipline variables obtained values, namely T count 5,276 > T table 1.689. Test results F obtained F count 59,893 > F table 2,77. The results showed that leadership and discipline both partially and simultaneously had a positive and significant effect on the